The Role of Cultural Heritage in Lifelong Learning – Selected Examples from European Countries - Hołuj, Dominika (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The article reviews the literature showing European experiences in executing educational projects using cultural heritage, analyses and aggregates their effects, assesses how the use of heritage increases educational effects and asks whether it contributes to the implementation of other ones. The analysis showed that activities using heritage implement objectives for which the idea of lifelong learning is carried out. The personal development of participants promotes social inclusion, the development of social bonds, civic engagement and the development of entrepreneurial attitudes. Particularly good effects are achieved when working with people from excluded groups, creative people and those interested in culture and history. Regardless of educational effects, projects contribute to the preservation and improvement of cultural heritage.